If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + -1) + 8 = -5(x + 7) Reorder the terms: -6(-1 + x) + 8 = -5(x + 7) (-1 * -6 + x * -6) + 8 = -5(x + 7) (6 + -6x) + 8 = -5(x + 7) Reorder the terms: 6 + 8 + -6x = -5(x + 7) Combine like terms: 6 + 8 = 14 14 + -6x = -5(x + 7) Reorder the terms: 14 + -6x = -5(7 + x) 14 + -6x = (7 * -5 + x * -5) 14 + -6x = (-35 + -5x) Solving 14 + -6x = -35 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 14 + -6x + 5x = -35 + -5x + 5x Combine like terms: -6x + 5x = -1x 14 + -1x = -35 + -5x + 5x Combine like terms: -5x + 5x = 0 14 + -1x = -35 + 0 14 + -1x = -35 Add '-14' to each side of the equation. 14 + -14 + -1x = -35 + -14 Combine like terms: 14 + -14 = 0 0 + -1x = -35 + -14 -1x = -35 + -14 Combine like terms: -35 + -14 = -49 -1x = -49 Divide each side by '-1'. x = 49 Simplifying x = 49
| -3(t-5)+5t=8t-3 | | 5p^2=-7p-2 | | 0.2(x+7)=8 | | 5(2p+3)=50 | | 11x-3x=4(7)-4 | | X^2+8x-768=0 | | 2x+3=2.5x+1 | | 22n+3p-15n= | | ((x+1)/(2x-5))=3/4 | | -6-c=2 | | 2y+3x-4x+2y= | | (x+1)/(2x-5)=3/4 | | e^9x+7=6 | | 11*6=23.60 | | x+14.3=42 | | 3x+8=2+48 | | x(x+2)=28 | | 4*(x*x)-8=56 | | -2(-15x-1)-5=6(5x-4)+30 | | -2(-15z-1)-5=6(5z-4)+30 | | x*x=98 | | 9n-3p+3p= | | x*x*x=98 | | 6y-8y+y= | | 2x-7y=-28 | | 15/7*y=3 | | 4x+30=12x-50 | | 1-4x=7-x | | 1-4x=7-x | | 26=22-4(3-4w) | | 9x-9y=0 | | (n-7)*8=16 |